PENGARUH PENDEKATAN PEMBELAJARAN DAN KEBUGARAN JASMANI TERHADAP HASIL BELAJAR KETERAMPILAN SEPAKBOLA (Studi Eksperimen pada Siswa SMA Labschool Kota Bandung) - Ricky Fernando (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This research seeks to examine the effectiveness of learning tactical and technical approach to the learning outcomes of football skills. Results of this study are expected to be used as an alternative solution in order to develop the quality of learning football. The method used in this study is the experimental method to the design of post-only design. The population in this study were students of class XI SMA Labschool son UPI Bandung as many as 60 students. The sampling technique using purposive sampling technique.When the study is over 2 months, the number of 18 treatment sessions, with a frequency of 1 week 3 times. Author chosen instrument is a test of football skill and playing ability test (GPAI) for high school students football skills tests (test start and end of the football skills) there are four authors use the test passing and stoping, heading, dribbling and shooting and playing ability test (GPAI). Based on the analysis, it can be concluded that: (1) there is a significant effect of learning tactical approach to the learning outcomes of football skills. (2) There is a significant effect of technical learning approach to the learning outcomes of football skills. (3) There are differences in the effect of tactical and technical learning approach towards learning outcomes football skills, but more tactical approach a significant impact on learning outcomes of football skills than technical learning approach.Keywords: learning approach tactical, technical learning approach, results learning skills football.